95.3k views
4 votes
What is (x-2)^2+(y+1)^2=4^2

1 Answer

7 votes

Answer:

y = sqrt(16 - (x - 2)^2) - 1 or y = -sqrt(16 - (x - 2)^2) - 1

Explanation:

Solve for y:

(x - 2)^2 + (y + 1)^2 = 16

Subtract (x - 2)^2 from both sides:

(y + 1)^2 = 16 - (x - 2)^2

Take the square root of both sides:

y + 1 = sqrt(16 - (x - 2)^2) or y + 1 = -sqrt(16 - (x - 2)^2)

Subtract 1 from both sides:

y = sqrt(16 - (x - 2)^2) - 1 or y + 1 = -sqrt(16 - (x - 2)^2)

Subtract 1 from both sides:

Answer: y = sqrt(16 - (x - 2)^2) - 1 or y = -sqrt(16 - (x - 2)^2) - 1

User MrYoshiji
by
6.5k points